2004
DOI: 10.1139/s04-018
|View full text |Cite
|
Sign up to set email alerts
|

First flush pollution load of urban stormwater runoff

Abstract: In a storm event, a first flush (FF) phenomenon occurs when most of the pollution load is transported in the initial part of the event discharged volume. The objectives of the study were to consider its severity for a number of pollutants as well as to recognize rainfall–runoff characteristics that influence it. The study was conducted in a semi-arid region of a mixed residential and commercial urban catchment in Iran. Ten major rainfall events were monitored for total solids (TS), total suspended solids (TSS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(46 citation statements)
references
References 4 publications
6
39
0
Order By: Relevance
“…As shown in Table 4, the FF 30 values of TP, TSS, and DCu were significantly positively related to rainfall, average rainfall intensity, and maximum rainfall intensity (p<0.05), which are similar to previous studies (Deletic 1998;Taebi and Droste 2004;Luo et al 2012). However, the FF 30 values for all the parameters studied were not correlated with the time of maximum rainfall intensity, which differs from the previous study.…”
Section: Temporal Changes In Pollution During Rainingsupporting
confidence: 88%
See 1 more Smart Citation
“…As shown in Table 4, the FF 30 values of TP, TSS, and DCu were significantly positively related to rainfall, average rainfall intensity, and maximum rainfall intensity (p<0.05), which are similar to previous studies (Deletic 1998;Taebi and Droste 2004;Luo et al 2012). However, the FF 30 values for all the parameters studied were not correlated with the time of maximum rainfall intensity, which differs from the previous study.…”
Section: Temporal Changes In Pollution During Rainingsupporting
confidence: 88%
“…Han et al (2006) reported that 30 to 35 % of the mass was contained in the first 20 % of the runoff. Deletic (1998) and Taebi and Droste (2004) concluded that the magnitude of FF is positively and significantly correlated to the maximum rainfall intensity.…”
Section: Introductionmentioning
confidence: 99%
“…In Naedongcheon (the upper part of the Mandae area) and Jungjohangcheon (the upper part of the Jaun area), the first flush is indicated by the SS, TP and BOD values. Although the first flush mostly occurs during storm events in highly paved watersheds in urban and mixed land use areas [14,17,23], the first flush phenomenon was identified in the agricultural region of this study, where excessive soil erosion occurs. The shape of the M(V) curve of the rainfall event occurring on 1-3 October in Jungjohangcheon is concave (Figure 6) because the rainfall intensity was high at the final stage of rainfall.…”
Section: M(v) Curve Fitting and First Flushmentioning
confidence: 70%
“…In addition to this, Deletic, 1998 andTaebi et al (2004) conducted research into early-stage storm water and reported that early-stage storm water phenomena are complicated and vary greatly according to regional characteristics [15,16]. According to Taebi et al (2004), it was reported that as the urbanized area and impervious area ratio were higher, the first flush effects were greater [16]. It is expected that in the case of runoff water reduced by filtration facilities, treating the overflows of early-stage rainfall when pollutant loads are relatively higher is the preferred method of maximizing the reduction of pollutant loads.…”
Section: Water Quality Analysismentioning
confidence: 97%
“…Sansalone et al (1997) defined it to be early stage storm water if the standard cumulative pollutant loads exceed the standard cumulative runoff curve [14]. In addition to this, Deletic, 1998 andTaebi et al (2004) conducted research into early-stage storm water and reported that early-stage storm water phenomena are complicated and vary greatly according to regional characteristics [15,16]. According to Taebi et al (2004), it was reported that as the urbanized area and impervious area ratio were higher, the first flush effects were greater [16].…”
Section: Water Quality Analysismentioning
confidence: 99%